En wie zorgt er voor de mantelzorger? Ondersteuning van mantelzorgers na opname van hun naaste - Ingrid Nordt (Journal of Social Intervention: Theory and Practice, 2012)
And who will take care of the caregiver? Supporting caregivers after the admission of a relative to a care facility The caregiver plays an important role in the care of relatives. Government policy is aimed to offer maximum support to caregivers in order to fulfill their role as caregivers as long as possible. But what happens if the care becomes too heavy and admission to a care facility is inevitable? This article discusses the support caregivers need after their relative is admitted to a care facility. A difficult period for caregivers in which they search for a new role in a new situation.